Implementasi Kurikulum Merdeka di Sekolah Indonesia: Sebuah Studi Literatur Tentang Peluang dan Tantangan : Penelitian - Wendi Rehan Situmorang; Jogi Situmorang; Gracelino Prasetyo Nainggolan; Mario Purba; Divo Valentino Siboro (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Merdeka Curriculum was introduced as a response to the need for educational transformation in Indonesia, emphasizing flexible, relevant, and student-centered learning. This study aims to map the implementation of the Merdeka Curriculum in Indonesian schools, identify patterns of practice, and examine supporting factors and challenges in the learning process. A qualitative literature review with thematic analysis was employed, examining scientific journals, proceedings, research reports, and books published in the last five years. The findings indicate that curriculum implementation varies across schools, influenced by teacher competence, school management support, and the availability of facilities. Schools with highly competent teachers, adaptive leadership, and adequate resources effectively implement differentiated learning, project-based activities, and authentic assessments, fostering student creativity, motivation, and character development. Conversely, limited teacher understanding, inadequate management support, and insufficient facilities pose significant barriers. The study highlights the importance of integrating teacher capacity, school support, and facility readiness, along with intensive mentoring and practice-based training, to ensure effective and sustainable implementation of the Merdeka Curriculum. These insights provide valuable guidance for educators, policymakers, and researchers to strengthen curriculum implementation and enhance the quality of education in Indonesia.